DAYA HAMBAT EKSTRAK BAWANG DAYAK (Eleutherine palmifolia (L.) Merr.) TERHADAP PERTUMBUHAN BAKTERI Lactobacillus acidophilus - Nadalia Malika Bilqis; Isyana Erlita; Deby Kania Tri Putri (Dentin, 2018)
ABSTRACTBackground: Lactobacillus acidophilus is bacteria which causes the advanced caries if it is ignored which will infect another tissue. Bawang dayak is a plant that is used as a traditional medicine which can inhibit the Lactobacillus acidophilus because it has compounds such as flavonoid, alkaloid, glycoside, phenolic, quinones, steroid, essential oils, and tannin. Purpose: The purpose of conducting this study is to find out the resistivity zone from Lactobacillus acidophilus after giving the bawang dayak extract of various concentrations. Method: This study applies a true experimental with posttest only with control group design with six treatment groups which are bawang dayak extract with the concentration of 20 mg/ml, 40 mg/ml, 60 mg/ml, 80 mg/ml, K(-) aquadest, and K(+) 2% of chlorhexidine digluconate. Maceration method is used to extract bawang dayak while diffusion method is used to test the resistivity and to measure the resistivity zone. Result: The result of the test that shows bawang dayak extract with the concentration of 20 mg/ml, 40 mg/ml, 60 mg/ml, and 80 mg/ml are obtained the average number of resistivity zone to 9,36 mm, 11,45 mm, 14,47 mm, 20,30 mm, and chlorhexidine digluconateis 15,33 mm. The data analysis of one-wayAnova and post-hoc LSD are obtained at (p<0.05) of bawang dayak extract which means that there is meaningful different to each treatment group. Conclusion: The resistivity zone of bawang dayak extract is higher than the positive control group which is 2% of chlorhexidine digluconate towards the growth of Lactobacillus acidophilus. ABSTRAKLatar belakang: Lactobacillus acidophilus merupakan bakteri pencetus karies lanjut yang apabila dibiarkan akan menginfeksi jaringan lainnya. Bawang dayak (Eleutherine palmifolia (L.) Merr.) merupakan tanaman yang digunakan sebagai obat tradisional yang dapat menghambat Lactobacillus acidophilus dikarenakan memiliki senyawa flavonoid, alkaloid, glikosida, fenolik, kuinon, steroid, minyak atsiri dan tannin. Tujuan: Mengetahui zona hambat dari bakteri Lactobacillus acidophilus setelah diberikan ekstrak bawang dayak dengan berbagai konsentrasi. Metode: Penelitian ini merupakan penelitian true experimental dengan post test only with control group design dengan 6 kelompok perlakuan,  yaitu ekstrak bawang dayak konsentrasi 20 mg/ml, 40 mg/ml, 60 mg/ml, 80 mg/ml, kontrol K(-) aquadest dan K(+) klorheksidin diglukonat 2%. Metode maserasi digunakan untuk mengekstraksi bawang dayak sedangkan uji daya hambat menggunakan metode difusi dan pengukuran zona hambat. Hasil: Hasil dari pengujian menunjukkan bahwa ekstrak bawang dengan konsentrasi 20 mg/ml, 40 mg/ml, 60 mg/ml, 80 mg/ml didapatkan rerata zona hambat 9,36 mm, 11,45 mm, 14,47 mm, 20,30 mm, dan klorheksidin diglukonat sebesar 15,33 mm. Analisis data One Way Anova diperoleh